Absence of nectar resource partitioning in a community of parasitoid wasps - Menz, M.; Brown, G.; Dixon, Kingsley; Phillips, R. (Kluwer Academic Publishers, 2015)
Parasitoid wasps occur in diverse communities, with the adults of most species sourcing carbohydrates from nectar or honeydew. However, the role of niche partitioning of nectar resources in maintaining diverse communities of parasitoid Hymenoptera is poorly known. To elucidate patterns of nectar resource use and test whether species partition resources, we investigated pollen loads in a community of parasitoid thynnine wasps in the biodiversity hotspot of southwestern Australia. In total, 304 thynnine wasps from 28 species were captured. Eighteen of these species are undescribed, highlighting the high diversity of unrecognized species in southwestern Australia. Pollen loads were detected on 111 individuals representing 19 species. Six pollen types were identified. All species that carried pollen primarily visited two tree species, Agonis flexuosa and Eucalyptus marginata, in the Myrtaceae. The other four pollen types were only recorded from single wasps. There was no evidence of nectar-resource partitioning. This may be due to these Myrtaceae producing abundant, open-faced flowers. Wasp species that were not recorded carrying pollen may utilise other carbohydrate sources, such as homopoteran honeydew. Niche partitioning is predicted to occur during the parasitoid larval phase of the life cycle. This study highlights the importance of nectariferous Myrtaceae in supporting diverse wasp communities. Further, two species of nectar-foraging wasps collected here are involved in the pollination of rare orchid species. Hence, conservation and management of habitats that support floriferous Myrtaceae are important for both the maintenance of diverse wasp communities, and the plants they pollinate.